Artificial Intelligence in Higher Education: An Analysis of Existing Bibliometrics - Roberto López-Chila; Joe Llerena-Izquierdo; Nicolás Sumba-Nacipucha; Jorge Cueva-Estrada (MDPI AG, 2023)
Since its origin in the 1950s, artificial intelligence (AI) has evolved from technological to educational applications. AI is emerging as an essential tool in education. Its integration into education promises the personalization and the globalization of learning. Despite its potential, it is crucial to consider its ethical challenges and uses. This bibliometric study sought to understand the current state of AI in higher education in order to provide a basis for future research. A bibliometric analysis was conducted between 2017 and 2023, using the Scopus database. The query was performed on 23 October 2023 and focused on titles, keywords, and abstracts. A total of 870 articles were found, and their metadata were analyzed after removing incorrect data. VOSviewer software was used to visualize the similarities, and the publications were studied by country, authors, and collaborations. A steady growth in AI studies in higher education was found, highlighting areas such as computer science and social sciences. China and the United States led in production and citations. Keywords such as "artificial intelligence", "chatgpt", and "machine learning" indicated trends and areas of interest.